A descriptive study of the perceptual knowledge of selected office employees on the use of CCTV surveillance systems as a tool for security in office spaces - Banes, Charissa B. (UP College of Home Economics, 2012)
This research was conducted in order to determine the perceptual knowledge of selected office employees on the use of CCTV surveillance systems as a tool for security in office spaces. The researcher employed the descriptive study design and used the quantitative method of data gathering in order to gather data which were later analyzed both quantitatively and qualitatively in relation to the specific objectives of the research. Ninety-eight (98) Filipino office employees who were at least 18 years old and working for at least a year within an office settling in Metro Manila which employs CCTV surveillance for security purposes were selected through purposive non-probability sampling and surveyed using a structured questionnaire with close-ended questions. Analysis of the results showed that in terms of using CCTV surveillance systems in office spaces, the perceived compliant areas were (a) those associated with office security concerns, and (b) those where low levels of privacy are usually observed. The respondents were divided on the concerns on privacy and ethics of use, although three definite concerns were identified. On the other hand, perceived capabilities of CCTV surveillance systems in terms of addressing security issues reflected limited knowledge on how the technology is used, while perceived technological capabilities of CCTV surveillance systems reflected ample knowledge regarding the matter. The findings generally suggest that although the respondents have a definite idea as to where they want CCTV surveillance to be used in office spaces, limited knowledge on how the technology is used lead to a perceptual knowledge which leans towards a possible overreliance on the technology and a skeptic view of the people who have control over the system.